2012
DOI: 10.4067/s0716-97602012000400013
|View full text |Cite
|
Sign up to set email alerts
|

Gastrodia elata Blume and its pure compounds protect BV-2 microglial-derived cell lines against β-amyloid: The involvement of GRP78 and CHOP

Abstract: This study reveals the protective effects of GE against β-amyloid-induced cell death, possibly through the enhancement of protein folding machinery of a representative protein, GRP78, and the regulation of CHOP in BV2 mouse microglial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Endoplasmic reticulum (ER) stress signaling was also involved in the Aβ-induced microglial activation and apoptosis. Lee et al ( 2012 ) found that the anti-apoptotic ER stress protein glucose-regulated protein 78 (GRP78), a marker for enhanced protein folding machinery, was decreased in Aβ-stimulated microglial cells, while pretreatment of gastrodin increased the expression of GRP78, revealing the protective effects of gastrodin was possibly achieved through the enhancement of protein folding machinery, thus attenuating the neurotoxic activities of microglial cells. Li and Qian ( 2016 ) found gastrodin could not only counteract Aβ 1 - 42 -triggered release of pro-inflammatory cytokines and nitric oxide (NO), but also attenuate Aβ 1 - 42 -induced apoptosis in primary neural progenitor cells (NPCs), and these effects were associated with the inhibition of MEK1/2 and JNK expressions.…”
Section: Effects Of Gastrodin On Cns Diseasesmentioning
confidence: 99%
“…Endoplasmic reticulum (ER) stress signaling was also involved in the Aβ-induced microglial activation and apoptosis. Lee et al ( 2012 ) found that the anti-apoptotic ER stress protein glucose-regulated protein 78 (GRP78), a marker for enhanced protein folding machinery, was decreased in Aβ-stimulated microglial cells, while pretreatment of gastrodin increased the expression of GRP78, revealing the protective effects of gastrodin was possibly achieved through the enhancement of protein folding machinery, thus attenuating the neurotoxic activities of microglial cells. Li and Qian ( 2016 ) found gastrodin could not only counteract Aβ 1 - 42 -triggered release of pro-inflammatory cytokines and nitric oxide (NO), but also attenuate Aβ 1 - 42 -induced apoptosis in primary neural progenitor cells (NPCs), and these effects were associated with the inhibition of MEK1/2 and JNK expressions.…”
Section: Effects Of Gastrodin On Cns Diseasesmentioning
confidence: 99%
“…A previous study demonstrated the neuroprotective effect of GE rhizome chloroform extract in vitro using rat pheochromocytoma (PC12) cells incubated with A β 1–42 [ 45 ]. In addition, methanol extract of GE rhizome and its pure components, gastrodin and 4-HBA, have been shown to have protective effects against A β -induced cell death in BV2 microglial cells, possibly through upregulation of glucose-regulated protein 78 (Grp78), an antiapoptotic endoplasmic reticulum (ER) stress protein related to protein-folding machinery [ 48 ].…”
Section: Protective Effects Of Ge and Its Components In Neurodegenmentioning
confidence: 99%
“…Studies utilizing a green fluorescent/Grp78 fusion protein reported targeting to mitochondria within a short period of ischemia-like stress [ 86 ]. Overexpression of Grp78 in BV2 mouse microglial cell lines [ 102 ] and astrocytes protected against ischemic injury and preserved respiratory activity and mitochondrial membrane potential after ischemic stress [ 103 ]. Pharmacological induction of Grp78 reduced neuronal loss in both forebrain and focal cerebral ischemia [ 104 , 105 ].…”
Section: Hsp70 and Bcl2 In Mitochondrial Homeostasismentioning
confidence: 99%